The flickering jaundice - Amrutha, Cynthia; Rai, Shipra (International Journal of Research in Medical Sciences, 2020)
Benign Recurrent Intrahepatic Cholestasis (BRIC) is a rare autosomal recessive disorder characterized by intermittent episodes of jaundice and pruritus. It is also known as Summerskill-Walshe-Tygstrup syndrome. It is a benign disease with no progression to end stage liver disease.. The first episode of cholestatic jaundice occurs early in life and there are asymptomatic periods between attacks lasting weeks to years. This case report presents a young male who presented with severe pruritus and acute onset jaundice. He had his first episode of jaundice at the age of twelve and had several intermittent episodes since then. Diagnosis was made by the unique clinical presentation with exclusion of other causes of cholestatic jaundice. This case report highlights the importance of detecting such cases of rarity and preventing unnecessary invasive diagnostic procedures on such patients.